Criminal records and conditional citizenship: towards a critical sociology of post-sentence discrimination - Henley, Andrew (EG Press Limited, 2017)
The critical sociology of punishment has a long-established tradition of exploring issues such as: the differential application of penal sanctions across class, race and gender divisions; the harms associated with confinement in penal and semi-penal institutions; and the expansion of the carceral continuum into community settings. More recently, North American scholarship has explored the extent to which criminalisation may generate a number of ‘collateral consequences’ for those previously subjected to punishment. However, this term arguably fails to convey what is at stake when those who have served their sentences are denied access to the full range of rights and entitlements associated with meaningful citizenship. Indeed, for many people with convictions, the discrimination which they face in their post-sentence lives may be experienced as equally or even more painful than the original sanctions for lawbreaking. Moreover, given the often precarious status of those targeted for punishment in many advanced capitalist economies, this discrimination against convicted population is likely to intensify and exacerbate pre-existing marginality. This requires that post-sentence disadvantage should be considered as central to the social process of punishment and not merely ‘collateral’ to it. In this short chapter, I provide a brief exploration of some the issues arising from criminal records within England and Wales. In doing so, I hope to demonstrate the potential for a broader sociological agenda concerned with discrimination against people with convictions during their post-sentence lives. That is, a field of enquiry which does not merely ‘chart’ different forms of discrimination against people with convictions, but which also: (1) explores the rationalities which underpin it; (2) examines the lived experience of those subjected to it; and therefore (3) opens up various forms of discrimination to critical scrutiny and contestation.